A theoretical investigation of the influence of gold nanosphere size on the decay and energy transfer rates and efficiencies of quantum emitters - Bradley, Louise (My University, 2016)
We present in this contribution a comprehensive investigation of the effect of the size of goldnanospheres on the decay and energy transfer rates of quantum systems placed close to these nanospheres. These phenomena have been investigated before, theoretically and experimentally, but no comprehensive study of the influence of the nanoparticle size on important dependences of the decay and energy transfer rates, such as the dependence on the donor-acceptor spectral overlap and the relative positions of the donor, acceptor, and nanoparticle, exists. As such, different accounts of the energy transfer mechanism have been presented in the literature. We perform an investigation of the energy transfer mechanisms between emitters and goldnanospheres and between donor-acceptor pairs in the presence of the goldnanospheres using a Green’s tensor formalism, experimentally verified in our lab. We find that the energy transfer rate to small nanospheres is greatly enhanced, leading to a strong quenching of the emission of the emitter. When the nanosphere size is increased, it acts as an antenna, increasing the emission of the emitter. We also investigate the emission wavelength and intrinsic quantum yield dependence of the energy transfer to the nanosphere. As evidenced from the literature, the energy transfer process between the quantum system and the nanosphere can have a complicated distance dependence, with a r−6 regime, characteristic of the Förster energy transfer mechanism, but also exhibiting other distance dependences. In the case of a donor-acceptor pair of quantum systems in the presence of a goldnanosphere, when the donor couples strongly to the nanosphere, acting as an enhanced dipole; the donor-acceptor energy transfer rate then follows a Förster trend, with an increased Förster radius. The coupling of the acceptor to the nanosphere has a different distance dependence. The angular dependence of the energy transfer efficiency between donor and acceptor exhibits a strong focusing effect and the same enhanced donor-dipole character in different angular arrangements. The spectral overlap of the donor emission and acceptor absorption spectra shows that the energy transfer follows the near-field scattering efficiency, with a red-shift from the localized surface plasmon peak for small sphere sizes.
PUBLISHED
Keywords: Gold; Energy Transfer